2012
DOI: 10.1378/chest.12-0330
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Beliefs About Lung Cancer Care

Abstract: Similarities and differences in beliefs about disease-directed treatment were observed between minority and nonminority patients with lung cancer. Minority patients hold more fatalistic views about the disease and misperceptions about advance care planning and hospice care. Further research is needed to assess the impact of these beliefs on decisions about lung cancer care and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 42 publications
0
72
1
Order By: Relevance
“…Prior research has shown that minority patients may hold beliefs different from those of nonminorities related to risk perception, fatalism, and fear of cancer diagnosis (13)(14)(15)(16). In particular, we found that blacks and Hispanics were more likely to hold fatalistic beliefs and that blacks were more likely to believe that surgery could cause lung cancer to spread (16).…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Prior research has shown that minority patients may hold beliefs different from those of nonminorities related to risk perception, fatalism, and fear of cancer diagnosis (13)(14)(15)(16). In particular, we found that blacks and Hispanics were more likely to hold fatalistic beliefs and that blacks were more likely to believe that surgery could cause lung cancer to spread (16).…”
mentioning
confidence: 50%
“…In particular, we found that blacks and Hispanics were more likely to hold fatalistic beliefs and that blacks were more likely to believe that surgery could cause lung cancer to spread (16).…”
mentioning
confidence: 84%
“…Factors contributing to the disparities in lung cancer include inequities in access to health care, differing perceptions regarding early detection, smoking cessation and treatment, and variation in susceptibilities to the effects of cigarette smoke (6,7). Conversely, the incidence rates for lung cancer among Hispanic men are much lower, and OS is better than in non-Hispanic whites.…”
Section: Disparitiesmentioning
confidence: 99%
“…Beliefs about care differed in a study with 335 lung cancer patients in relation to their ethnic backgrounds [110], as did symptom burden in another study involving 980 patients with pulmonary carcinoma [111]. In a recent study, MARTIN et al [112] highlighted significant differences in terms of various therapeutic aspects across ethnic groups in 5044 patients with lung or colorectal carcinoma.…”
Section: Cultural Dimensionmentioning
confidence: 99%